Identification of Human Walking Balance Controller Based on COM-ZMP Model of Humanoid Robot - Yoshikawa, Taizo (Frontiers in Robotics and AI, 2022)
The purpose of this research is to build a technology that enables wearable robotic systems that support human movement to maintain stable balance. By expanding our knowledge of conventional human gait analysis technology and robotics technology, we will build a technology that can estimate the state of human balance. In order to build a technology for estimating the human balance state based on the balance control technology of humanoid robots, we conducted joint research with Osaka University. We applied our knowledge of humanoid robot control to human stepping and braking motions, and confirmed the effectiveness of the balance control model using data measured by a motion capture system and a floor reaction force sensor system. In order to build a technology for estimating the human balance state based on the balance control technology of humanoid robots, we conducted joint research with Osaka University. We applied our knowledge of humanoid robot control to human stepping and braking motions to build a human balance control model. We confirmed the effectiveness of the balance control model using data measured by a motion capture system and a floor reaction force sensor system. In order to understand the state of human walking, the human walking motion was measured by motion capture and analyzed in detail. Following the norms of gait analysis techniques, we extended the balance control model of human foot-stepping and braking motions to a gait model that includes continuous straight-line walking and change of direction during walking. The effectiveness of the constructed balance control model was confirmed using a motion capture system and a floor reaction force sensor system.